2016
DOI: 10.1002/mdc3.12337
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Thalamic Deep Brain Stimulation for Essential Tremor: Clinical Outcome and Stimulation Parameters

Abstract: Background: The reasons underlying the loss of efficacy of deep brain stimulation (DBS) of the thalamic nucleus ventralis intermedius (VIM-DBS) over time in patients with essential tremor are not well understood. Methods: Long-term clinical outcome and stimulation parameters were evaluated in 14 patients with essential tremor who underwent VIM-DBS. The mean AE standard deviation postoperative follow-up was 7.7 AE 3.8 years. At each visit (every 3-6 months), tremor was assessed using the Fahn-Tolosa-Marin tremo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…In addition, in most cases of ET, the tremor score worsens over time, and the average tremor severity increases each year [ 10 ]. Previous studies have found that the benefits of DBS are affected by laterality and stimulation parameters [ 11 , 12 ]. Ondo et al concluded that unilateral thalamic DBS is less effective than bilateral DBS in controlling appendicular and midline ET [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in most cases of ET, the tremor score worsens over time, and the average tremor severity increases each year [ 10 ]. Previous studies have found that the benefits of DBS are affected by laterality and stimulation parameters [ 11 , 12 ]. Ondo et al concluded that unilateral thalamic DBS is less effective than bilateral DBS in controlling appendicular and midline ET [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ondo et al concluded that unilateral thalamic DBS is less effective than bilateral DBS in controlling appendicular and midline ET [ 11 ]. Moreover, a previous study found that to optimize tremor control, the stimulation parameters, including the voltage, frequency, and pulse width, need to be adjusted [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, our animal model is representative of a particularly resistant kind of obesity, which could potentially benefit from NAcc-DBS depending on the genetic background. We selected the DBS parameters for three main reasons: the success obtained in previous approaches using bilateral DBS [ 23 , 24 ] and similar stimulation protocols [ 22 , 27 , 34 , 69 ]; the tolerance associated with continuous DBS treatments [ 70 , 71 ]; and the technical difficulties in obtaining portable rat stimulators in our facilities. Nevertheless, DBS protocols which were closer to the current clinical scenario may reveal larger differences in weight gain [ 22 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tremor control from Vim stimulation appears to worsen over time [33][34][35][36]. In one series, 73% of patients had experienced waning stimulation benefit within 5 years of implantation [36].…”
Section: Vim Stimulationmentioning
confidence: 99%